The Effect of Balloon Blowing on the Frequency of Relapse in Children with Bronchial Asthma at Dr. H. Abdul Moeloek Lampung Province in 2024 - Liani, Desna; Antoro, Budi; Erwin, Tubagus (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
Introduction: Triggers of bronchial asthma can be in the form of air that has viruses, dust, cigarette smoke, individual mental obstacles/stress, and fatigue due to actual activities or work. Asthma that occurs afterwards often occurs if not treated immediately, it can cause shortness of breath to recur. One of the treatments that can overcome shortness of breath recurrence is wind blowing treatment. Wind blowing treatment, if given regularly, is very effective in curing shortness of breath recurrence. Purpose: The purpose of this study was to determine the effect of wind blowing on shortness of breath recurrence (recurrence) in children with bronchial asthma at Dr. H. Abdul Moeloek Bandar Lampung Hospital in 2024. Methode: Quantitative research type, semi-exploratory design, with the One Group Pre Test-Post Test Configuration approach. The population and illustrations in this study are all mothers who have children with Bronchial Asthma at Dr. H. Abdul Moeloek Bandar Lampung Hospital in 2024 from January to March with a total of 34 children. In this study, the testing procedure used was Purposive Testing. Result: Based on the test results, it is known that the average (average) asthma recurrence in children with bronchial asthma before being given intervention is 2.88 and after being given intervention is 1.82. Conclusion: Based on the measurement test, a p-value of 0.000 or a p-value of 0.05 was obtained so that it can be concluded that there is an effect of blowing on the incidence of asthma recurrence in children at Dr. H. Abdul Moeloek Bandar Lampung Hospital in 2024. It is hoped that the results of this research can be used as health data so that it can increase respondents' knowledge about the effect of blowing on the incidence of asthma recurrence in children, and it is hoped that parents will be more active in doing blowing properly. Not only that, but also so that parents can act calm and understand if their child experiences an asthma attack.